Corporate governance reforms and financial reporting quality at Middle East stock markets - Husseinali, Ahmed; Cheng, Fan Fah; Ramadili, Shamsher Mohamed; Chowdury, Taufiq Hassan Shah (IJECM, 2016)
This research aims to provide empirical evidence about the effect of corporate governance (CG) reform on the financial reporting quality (FRQ). Using a sample of non-financial firms listed at Saudi stock market (TADAWAL), Abu Dhabi securities market (ADX) and Qatar stock market the study investigated the trend of the quality of the financial reporting at theses stock markets before and after corporate governance reforms that applied to the listed firms. This study adopts the working capital accruals quality as a measurement of the financial reporting quality that can determine the level of the efficiency and the effectiveness of the promoted reform of corporate governance. Panel data method was applied to McNicholas model (2002) to calculate firms FRQ. Independent sample t-test was performed to investigate the trend of the FRQ in the selected countries and to examine the significance degree of the differences between the means for the periods before and after the applied corporate governance reform. The result shows that the applied corporate governance reform was efficient and the FRQ improved for the era after corporate governance reform in the Middle East stock markets. In addition the result shows the level of the similarities and the variations between the stock market in Middle East region.